New genus and species of Baetidae (Insecta: Ephemeroptera) from Brazil - Cruz, Paulo Vilela; Salles, Frederico Falcão; Hamada, Neusa; Falcão, Jesine Netto (Zootaxa, 2020)
One new taxon was brought to light during an Ephemeroptera survey in Roraima state, but it was not described. This new taxon was included in a cladistics analysis (as Gen A) in order to delimitate some Baetidae genera, and it was recovered as a new genus. Taking in account that the new genus and species status were already defined in a previously published paper, the objective of this study was to describe it based on imagoes and nymphs, and formally name it as Macuxi tunamore gen. nov. sp. nov. The new genus is sister group of Rhopyscelis Cruz, Salles & Hamada + Varipes Lugo-Ortiz & McCafferty clade, and can be differentiated from both mainly by the absence of long and stout setae on femora of all legs. Several characteristics were obtained in the morphological analyses to distinguish the new genus from other genera, but the paraglossa and glossa with pectinate setae, and claw with two rows of denticles, one reduced and other with apical ones larger than the others, are highlighted.